2013
DOI: 10.1016/j.cell.2013.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Functional Genomic Analyses Implicate Specific Molecular Pathways and Circuits in Autism

Abstract: Genetic studies have identified dozens of autism spectrum disorder (ASD) susceptibility genes, raising two critical questions: 1) do these genetic loci converge on specific biological processes, and 2) where does the phenotypic specificity of ASD arise, given its genetic overlap with intellectual disability (ID)? To address this, we mapped ASD and ID risk genes onto co-expression networks representing developmental trajectories and transcriptional profiles representing fetal and adult cortical laminae. ASD gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

114
1,107
1
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 956 publications
(1,228 citation statements)
references
References 81 publications
114
1,107
1
6
Order By: Relevance
“…Supporting our above hypothesis is a recent study on specific molecular pathways and circuits in autism, where ASD and ID risk genes were mapped onto co-expression networks of developmental trajectories and transcriptional profiles in the fetal and adult cortical laminae. 34 These studies showed bioinformatically that FMRP interacts with a series of ASD genes, one of them being MBD5. 34 Finally, we show that the expression levels of NR1D2 and CRY2 were significantly reduced in 2q23.1 deletion syndrome, SMS, and FXS LCLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting our above hypothesis is a recent study on specific molecular pathways and circuits in autism, where ASD and ID risk genes were mapped onto co-expression networks of developmental trajectories and transcriptional profiles in the fetal and adult cortical laminae. 34 These studies showed bioinformatically that FMRP interacts with a series of ASD genes, one of them being MBD5. 34 Finally, we show that the expression levels of NR1D2 and CRY2 were significantly reduced in 2q23.1 deletion syndrome, SMS, and FXS LCLs.…”
Section: Discussionmentioning
confidence: 99%
“…34 These studies showed bioinformatically that FMRP interacts with a series of ASD genes, one of them being MBD5. 34 Finally, we show that the expression levels of NR1D2 and CRY2 were significantly reduced in 2q23.1 deletion syndrome, SMS, and FXS LCLs. Interestingly, loss of CRY2 has been linked to high anxiety, and NR1D2 was recently shown to protect normal metabolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is focused on a specific neurodevelopmental disorder-ASD-because it has been suggested that ASD has its roots in abnormalities in prenatal brain development (50)(51)(52). Specifically, our analysis of the temporal expression patterns of coexpressed gene modules in the developing brain shows that genes in three EGenriched coexpression modules implicated in ASD are expressed at a high level at the earliest stages of brain development, as early as 8 weeks after conception.…”
Section: B C Amentioning
confidence: 99%
“…Co-expression networks seeded with genes recurrently mutated in autism were found to converge with networks in deep layer projection neurons of the prefrontal and primary motorsomatosensory cortex during midfetal development [193]. Parikshak et al [194] mapped autism risk genes to transcriptional networks throughout development and identified glutamatergic neurons in upper cortical layers as a critical cell type and brain region in autism. Undoubtedly, pathway and related network analyses have identified some degree of convergence with regard to potential mechanisms in which genes may participate, but, at present, these mechanisms remain fairly broad.…”
Section: Autism Genetic Studies May Point To Convergentmentioning
confidence: 99%